New Media, New Relationship to Participation? A Closer Look at Youth News Repertoires and Political Participation. (March 2018) - Edgerly, Stephanie; Vraga, Emily K.; Bode, Leticia; Thorson, Kjerstin; Thorson, Esther
This study extends past research on the relationship between news use and participation by examining how youth combine news exposure across an array of media devices, sources, and services. Results from a national survey of U.S. youth ages 12 to 17 reveal four distinct news repertoires. We find that half of youth respondents are news avoiders who exhibit the lowest levels of participation. The other half of youth respondents are characterized by one of three patterns of news use, each distinct in how they seek out (or avoid) using new media platforms and sources for news, and in their levels of participation.